1993
DOI: 10.3382/ps.0722166
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Content of Carcass Parts from Broilers Reared Under Cycling High Temperatures

Abstract: A study was conducted in which carcass parts from broilers reared under different growing temperature regimens were examined for crude protein, fat, calcium, phosphorus, potassium, and sodium. Commercial broilers were reared from 22 to 49 days of age at either 23.9 C constant temperature (thermoneutral) or 23.9 to 35 C cycling high temperature (heat stress). Birds in the heat stress environment were exposed to 8 h of 23.9 C, 4 h of 23.9 to 35 C, 4 h of 35 C, and 9 h of 35 to 23.9 C. Within each growth environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…In this experiment, broilers undergoing AHS treatment at 33 °C for 12 h displayed a significant reduction in the eviscerated percentage. Smith [ 23 ] found that the dry matter contents of carcass parts (breast and thigh) were significantly decreased by elevated environmental temperature, but the contents of Na (breast) and K (back, breast, drumstick, and thigh) were significantly increased, indicating that elevated environmental temperature may decrease the organic matter contents in the carcass of broilers, which may partly explain why hot environmental temperature decreased the eviscerated carcass percentage. Excitingly, we found that adding EGCG to the diet can significantly reduce the negative effects of AHS on the eviscerated carcass percentage.…”
Section: Discussionmentioning
confidence: 99%
“…In this experiment, broilers undergoing AHS treatment at 33 °C for 12 h displayed a significant reduction in the eviscerated percentage. Smith [ 23 ] found that the dry matter contents of carcass parts (breast and thigh) were significantly decreased by elevated environmental temperature, but the contents of Na (breast) and K (back, breast, drumstick, and thigh) were significantly increased, indicating that elevated environmental temperature may decrease the organic matter contents in the carcass of broilers, which may partly explain why hot environmental temperature decreased the eviscerated carcass percentage. Excitingly, we found that adding EGCG to the diet can significantly reduce the negative effects of AHS on the eviscerated carcass percentage.…”
Section: Discussionmentioning
confidence: 99%
“…Prime cuts yield included whole breast yield (with skin and bones) and leg yield (thighs and drumsticks with bones and skin), also calculated relative eviscerated carcass weight. The abdominal fat around the cloaca, cloacal bursa, gizzard, proventriculus and adjacent abdominal muscles was removed and weighed, as described by Smith (1993).…”
Section: Effects Of Methionine Source Arginine:lysine Ratio and Sodimentioning
confidence: 99%
“…As general inference, birds of HS-S environment had significantly (P0.05) less values of carcass, thighs and wing weights and dressing percentage and significantly (P0.05) heavier inedible weight than those of HS-M environment (Table , 2). The reports indicated that heat stress increased breast muscles percentages (Leenstra and Cahaner, 1992), reduced thighs weight (Smith, 1993) or decreased abdominal fat (ELDeeb and Abou-Elmagd, 2001). The reduction of thighs weight in the present study under severe heat stress (HS-S) agreed with Smith (1993).…”
Section: Carcass Characteristicsmentioning
confidence: 99%
“…The reports indicated that heat stress increased breast muscles percentages (Leenstra and Cahaner, 1992), reduced thighs weight (Smith, 1993) or decreased abdominal fat (ELDeeb and Abou-Elmagd, 2001). The reduction of thighs weight in the present study under severe heat stress (HS-S) agreed with Smith (1993). The reduction of carcass weight and dressing percentages were in agreement with the results of BWT (Table , 1).…”
Section: Carcass Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation